SWOT Analysir of Henna Cultivation in Arid Fringe of Rajas I an - Chand, Khem; Jangid, B L; Rao, S S; Singh, Y V (Annals of Arid Zone, 2016)
A "udy w", oonducted to onalyze mrengtbs, weakn""",,, opportuniti'" I'nd threa" in henna cultivation and trade in arid fringe of Rajasthan. Required information w~s collected through a sample (n = 100) survey of henna cultivating farmers and other sfukeholders, henna processors (n = 45), traders and market officials through structured and semi-structured interviews in Pali district during 1999-2005.The major strengths of henna CUltiva~oninclude assured production and employment generation, drought resistance, free from bird and animal damage,. and availability of regulated market. The major weaknesses are high uctuations in henna price, rain at harvest that spoils the produce quality, high labor cost and non availability of laboratory facility for quality testing. Future prospects for henna cultivation lie in the rising preferences for natural dyes and large export potential. The major thre~ts include competition with synthetic dye products, non-availability of labor at critical time, +d damage by semi-looper pest. It is concluded that strengths and opportunities of henna crop are strong enough to boost its growth in semi-arid Rajasthan and establish it as a !sustainable livelihood enterprise . Key words: Henna, production, quality, marketing, processing, demand, export.